2011
DOI: 10.1177/1040638711416623
|View full text |Cite
|
Sign up to set email alerts
|

Fast measurement of serum amyloid A in different specimens from swine by using a new one-step time-resolved fluorescent immunoassay

Abstract: Abstract. The objective of the present study was to develop a one-step, fast, competitive time-resolved fluorescent immunoassay to determine porcine serum amyloid A (SAA) by using species-specific reagents. The assay consisted of an all-in-one format involving only 55 min of incubation that was adapted and validated for use in 3 different specimens: serum, saliva, and meat juice. The method had overall within-and between-run coefficients of variation under 8% and 12%, respectively, and coefficients of determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Levels can also be detected in saliva using different techniques including fluorescent immunoassays (157). …”
Section: Acute Phase Proteinsmentioning
confidence: 99%
“…Levels can also be detected in saliva using different techniques including fluorescent immunoassays (157). …”
Section: Acute Phase Proteinsmentioning
confidence: 99%
“…In fact, the use of saliva as an analytical tool in porcine research has increased exponentially over the last years according to the PubMed database. Several studies have indicated that salivary acute phase protein (APP) concentrations can be utilized as early indicators of the health status of pigs (2, 3). This statement is of great value taking into account that some diseased pigs did not develop leucocytosis in spite of having clinical signs and pathological lesions but experienced an evident increase in APPs (4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…While the concentration of SAA in the serum is typically 1.0–10 μg/mL in healthy individuals, it has been observed to increase up to 1 mg/mL during illness . Previous studies in the literature have determined the measurements of SAA in swine samples of serum and saliva using a time-resolved fluorescent immunoassay (TR-FIA) …”
Section: Resultsmentioning
confidence: 99%